Roles of microglia in adult hippocampal neurogenesis in depression and their therapeutics - Fang, Shaoyi; Wu, Zhibin; Guo, Yali; Zhu, Wenjun; Wan, Chunmiao; Yuan, Naijun; Chen, Jianbei; Hao, Wenzhi; Mo, Xiaowei; Guo, Xiaofang; Fan, Lili; Li, Xiaojuan; et al. (Frontiers in Immunology, 2023)
Adult hippocampal neurogenesis generates functional neurons from neural progenitor cells in the hippocampal dentate gyrus (DG) to complement and repair neurons and neural circuits, thus benefiting the treatment of depression.Increasing evidence has shown that aberrant microglial activity can disrupt the appropriate formation and development of functional properties of neurogenesis, which will play a crucial role in the occurrence and development of depression.However, the mechanisms of the crosstalk between microglia and adult hippocampal neurogenesis in depression are not yet fully understood. Therefore, in this review, we first introduce recent discoveries regarding the roles of microglia and adult hippocampal neurogenesis in the etiology of depression. Then, we systematically discuss the possible mechanisms of how microglia regulate adult hippocampal neurogenesis in depression according to recent studies, which involve toll-like receptors, microglial polarization, fractalkine-C-X3-C motif chemokine receptor 1, hypothalamic-pituitary-adrenal axis, cytokines, brain-derived neurotrophic factor, and the microbiota-gut-brain axis, etc. In addition, we summarize the promising drugs that could improve the adult hippocampal neurogenesis by regulating the microglia. These findings will help us understand the complicated pathological mechanisms of depression and shed light on the development of new treatment strategies for this disease.